PERENCANAAN SALURAN DRAINASE KAWASAN PERUMAHAN MAHAKAM GRANDE KOTA SAMARINDA - SISWANTO, BAYU ARGO (KURVA S JURNAL MAHASISWA, 2018)
Along with the rapid development that occurred in the city of Samarinda resulted in the reduction of vacant land that can be used to absorb water into the soil. This leads to a decrease in the ability of the soil to absorb water as a result of land use change in the area of Mulawarman Residence Housing located on South Ringroad St., Samarinda Ulu. Hydrological analysis is conducted based on rainfall, topography area, characteristics of drainage area and flood frequency of the plan by using hydrological analysis obtained by the amount of water discharge that must be accommodated by drainage channel. Then on the basis of the discharge obtained, the drainage dimension can be planned based on the hydraulics calculations.